Effects of urbanization and land expropriation on the livelihoods of peri-urban farmers in North Wollo Zone, Ethiopia - Mesele Belay Zegeye; Moges Asmare Sisay; Dagnaw Beza Ayalew (PLoS ONE, 2025)
The aim of this study was to examine the effects of urbanization and land expropriation on the livelihoods of Peri-urban farmers in North Wollo Zone, Ethiopia. Data were collected from 378 peri-urban farmers using a structured questionnaire and multistage sampling. Qualitative data were obtained through focus group discussions and key informant interviews. A binary logistic regression model was used to identify factors influencing livelihood diversification among expropriated farm households. The results revealed a significant trend of expropriation without fair compensation, stemming from the disregard of legal procedures of expropriation and compensation in the study area. On average, 33.06% of respondents were fully expropriated and evicted, while the majority (66.94%) lost only part of their agricultural land. Expropriated farmers faced numerous challenges during their livelihood diversification, including high inflation, lack of urban living skills, informal land sales at low prices, misuse of compensation, displacement, family conflicts, social disruption, and skill gaps. They also blamed that they did not get any government support in properly utilizing compensation money for livelihood diversification. The Logit model results showed that livelihood diversification is positively influenced by factors such as the household head’s education, marital status, access to alternative land, fair compensation, off-farm employment, training, social networks, and livestock assets. It is negatively affected by farming as the primary occupation, household size, and expropriated land size. The study recommends that the government should help families of expropriated household’s secure sustainable livelihoods through fair compensation and proper support.